Perceived organizational support and teacher motivation - Connie Cassy Ompok; Lydia Teo (Secholian Publication, 2021)
Rural schools that lack of basic facilities and infrastructure is the focus of the study. With this ruralism conditions, teachers in rural primary school face many obstacles and challenges that could hinder their motivation. These might affect their teaching effectiveness. This study was intended to determine perceived organisational support on teacher motivation. The research sample consisted of 138 teachers in Sabah that directly become the respondents of the study. Data was obtained via questionnaire which was consisted of perceived organisational support: 17 items; and teacher motivation: 5 items). With success rate of 74% returned questionnaire and 102 fit to be evaluated, the data revealed that there was a strong correlation between perceived organisational support on teacher motivation. Teachers should be given support in order to enhance or maintain their motivation especially in rural condition.